Dye chromoendoscopy leads to a higher adenoma detection in the duodenum and stomach in patients with familial adenomatous polyposis - Hüneburg, R.; Heling, D.; Kaczmarek, D. J.; van Heteren, P.; Olthaus, M.; Fimmers, R.; Berger, M.; Coch, C.; Lau, J. F.; Kristiansen, G.; Weismüller, T. J.; Spier, I.; Aretz, S.; Strassburg, C. P.; Nattermann, J. (Endoscopy International Open, 2020)
Backround and study aims Duodenal cancer is the cancer most often seen in patients with familial adenomatous polyposis (FAP) who have undergone risk-reducing colonic surgery. Almost all patients with FAP eventually develop duodenal adenomas and risk for duodenal cancer is up to 12 % with poor prognosis. In addition, there is a rising concern regarding increased gastric cancer risk in patients with FAP. Our aim was to enhance polyp detection by using CE (CE) with the application of indigo carmine dye.Patient and methods We conducted a prospective, blinded study of patients with FAP undergoing endoscopic examination of the upper gastrointestinal tract. First, a standard white-light examination (WLE) was done followed by an examination performed by an endoscopist who was blinded to the previous examination, using chromoendoscopy (CE) (0.4 % indigo carmine dye).Results Fifty patients were included in the study. Using WLE, a median number of 13 adenomas (range 0–90) was detected compared to 23 adenomas/patient (range 0–150; P < 0.0001) detected after staining, leading to a higher Spigelman stage in 16 patients (32 %; P = 0.0003). CE detected significantly more larger adenomas (> 10 mm) than WLE (12 vs. 19; P = 0.0391). In the gastric antral region, a median number of 0 adenomas (range 0–6) before and 0.5 adenomas (range 0–7) after staining (P = 0.0025) were detected.Conclusion This prospective endoscopic trial, to our knowledge the largest in patients with FAP, showed a significant impact of CE on adenoma detection and therapeutic management in the upper gastrointestinal tract. This leads to more intensive surveillance intervals.